Multivariate analysis to mensuration pH and electrical conductivity of soil cultivated with beet in function of water blades and salinity levels (Research, Society and Development, 2020)
The objective was to analyze the pH and electrical conductivity of the soil solution as a function of water blades and salt levels after beet cultivation. The experiment was conducted in a randomized block design, with treatment of four levels of electrical conductivity (S1= 0.12, S2= 2.12, S3= 4.12 e S4= 6.12 dS m-1) and three water blades: L1= 50; L2= 100 e L3= 150% da ETc (culture evapotranspiration). The analyzes were performed at the Soil Chemistry Laboratory, Campus de Arapiraca, UFAL. Where soil pH in water and potassium chloride was determined: pH-H2O (PHA) and pH-KCl (PHK), exchangeable acidity (ACT), potential (ACP) acidity and the electrical conductivity of the soil (CE). The results showed that the pH-H2O increased linearly with the water blades and decreased with the levels of salinity, the opposite occurring with the factor blade in the pH-KCl, both of which had a description up to the threshold of 3.12 dS m-1. The exchangeable and potential acidity and electrical conductivity of the soil solution grew with decreasing blades and increased salinity. In PCA, exchangeable acidity was better at all salinity levels and pH-KCl for the S4 level. Howeve, the L3 blade with the lowest influence on the variables within the salinities. Cluster grouping, scatter plots, confidence regions, histogram, density estimate and ellipses showed a positive correlation between the electrical conductivity variable and the salinity fator.